Sleep Ethics in the Hadith as a Basis for Developing Sleep Hygiene for Modern Mental Health - David Ariansyah; Rahmi Susanti; Maya Anjeli; Ahmed Eltamimi (Hamidah: Jurnal Ilmu Hadis, 2025)
The increasing prevalence of sleep disorders, which directly impacts the decline of modern mental health, indicates a gap in the technical approach to sleep hygiene, which lacks a foundation in values. Therefore, a conceptual contribution based on normative traditions is needed to strengthen healthy sleep practices. This study aims to identify ethical themes related to sleep in the hadith and formulate a conceptual model of sleep hygiene based on prophetic values that align with contemporary principles of mental health. Using a qualitative literature study method, the study employs a systematic thematic analysis of hadiths from Kutub al-Tisʻah, involving initial coding, categorization, and cross-source integration, accompanied by triangulation of health psychology literature as a connecting framework. The results show five consistent and recurring ethical themes in the hadith texts: first, regulating sleep-wake rhythms in harmony with natural cycles; second, moderation of sleep duration as a form of physiological discipline; third, pre-sleep etiquette including physical hygiene, psychological calm, stimulus reduction, and preparation routines; fourth, choosing a safe and stable sleeping position to support physiological regulation; and fifth, orientation to self-awareness through prayer, introspection, and spiritual framing that organizes mental readiness. These five themes can be systematically mapped to the components of modern sleep hygiene, including circadian regulation, sleep environment management, routine stability, and pre-sleep stress management. This integration yields a three-component model that emphasizes the synchronization of biological rhythms, reinforces behavioral discipline, and promotes the internalization of value-based preventive habits. This provides a theoretical foundation for the development of behavioral interventions and mental health promotion, which warrants further empirical testing.